Identification of estrogen-responsive genes based on the DNA binding properties of estrogen receptors using high-throughput sequencing technology - Ikeda, Kazuhiro; Horie-Inoue, Kuniko; Inoue, Satoshi (Acta pharmacologica Sinica, 2015)
Estrogens are important endocrine hormones that control physiological functions in reproductive organs, and play a pivotal role in the generation and progression of breast cancer. Therapeutic drugs including anti-estrogen and aromatase inhibitors are used to treat patients with breast cancer. The estrogen receptors, ERa and ERβ, function as hormone-dependent transcription factors that directly regulate the expression of their target genes. Therefore, a better understanding of the function and regulation of estrogen-responsive genes provides insight into the gene regulation network associated with breast cancer. Recent technological developments in high- throughput sequencing have enabled the genome-wide identification of estrogen-responsive genes. Further elucidating the estrogen gene cascade is critical for advancements in the diagnosis and treatment of breast cancer.